The piano teacher [large type] - Lee, Janice Y. K. (Thorndike Press large print reviewer's choice, 2009)
Hired by the wealthy Chen family as a piano instructor, Claire Pendleton is seduced by the social life of Hong Kong's expatriate community and begins an affair with Will Truesdale, an enigmatic Englishman with a devastating past.